Organisational Code-Switching as a Catalyst: Unveiling the Effect of Mixed-Curriculum Management on English-Medium School Performance - Akuba, Stefy; Sinaga, Poltak; Ugut, Gracia; Budiono, Sidik (Migration Letters, 2024)
This study employs a quantitative research design to comprehensively investigate the integrative knowledge-based theory approach to mixed curriculum management and the performance of English-medium schools. It proposes a model incorporating organisational code-switching to mediate between mixed-curriculum management and school performance. English-medium schools, spanning from kindergarten to high school levels and employing national and international curricula, serve as the focal point of this research. A structured survey instrument collected data from 457 senior leadership team members representing 119 English-medium schools. The analysis employed Partial Least Square Structural Equation Modelling (PLS-SEM), with the AMOS 24 data analysis software utilised for processing. The findings indicate a direct connection between curriculum acquisition and school performance did not yield a significant result. Consequently, the study emphasises the importance of involving organisational code-switching as a mediator to enhance school performance in this context.